Sulphate soil stabilisation with magnesium binders for road subgrade construction. Issue 6 (12th May 2022) - Seco, A.; del Castillo, J.M.; Espuelas, S.; Marcelino, S.; García, B.
ABSTRACT : This paper analyzes the ability of magnesium oxide-based additives to stabilise a low bearing gypsum marly soil, in order to reach subgrade requirements. This soil was not adequate for stabilisation with lime or cement because of its high sulphate content. Binders considered in this investigation were composed of three reactive Mg products and by products, both with and without ground granulated blast furnace slags (GGBS). They were compared to two cements and an aerial lime as soil stabilisers in a laboratory investigation and a field trial. Laboratory tests showed that Mg products with GGBS reached strength results close and at times even better than those of cement. One of the Mg products was the only additive able to reduce the natural soil swelling. Leaching tests demonstrated the ability of the Mg products to reduce the soil leaching of substances like calcium, magnesium, sulphate and chloride. In field trials two of the Mg products combined with GGBS met the bearing capacity requirements for subgrades, in accordance with the Spanish standard.